Efficiency of the cloacal sexing technique in greater rhea chicks (Rhea americana) - Bazzano, Gisela del Valle (2012)
1. The feasibility and accuracy of the cloacal sexing technique in greater rhea chicks was assessed using chicks of two captive populations of greater rhea in Córdoba, Argentina. 2. A total of 46 greater rhea chicks of 2 to 3 months of age were randomly arranged into three groups and the members of each group were sexed by a different operator. 4. A feather of each chick was plucked for sexing through a molecular method and results were used as controls. 5. Sex was correctly assigned by cloacal inspection in 98% of the cases. Chick manipulation was easily performed and no infections or traumatic lesions were observed a posteriori. 6. Cloacal sexing of rhea chicks up to 3 months of age does not affect animal welfare and should be considered an efficient alternative to molecular methods.